Barries to intimate relationships amongst young men with physical disability in Nepal. - Das, Prakash Lal (2011)
ABSTRACT: Disability is neither restricted to one social or economic group, nor to any culture, race, gender, nor age, since anyone can be born with a disability or can acquire one at any time. Despite the loss of functional mobility, the physical and emotional aspects of intimacy continue to be as important for disabled as they are for non-disabled people. For men with mobility impairments in Nepal, such needs are largely unmet. The aim of this study was to explore how young men in Nepal who have a physical disability consisting of mobility impairment perceive their ability to develop intimate relationships. Five Participants in this study were recruited from single young men ages 18 to 30 whose physical disability consisted of mobility impairment. Semi-structured interviews were conducted and examined by means of manifest content analysis. Findings showed that young men with mobility impairments face limitations and barriers from negative societal attitudes (such as lack of awareness about disabled people, social stigma, and unequal opportunities) and personal aspects preventing the establishment of relationships (reduced mobility due to physical weakness, low self-esteem, and limited income) that together hinder them from developing intimate relationships. The barriers to developing intimate relationships perceived by the young men in this study comprise challenging issues that need greater attention from society. Our findings may help to mainstream the needs of physically disabled people who have been marginalized in Nepal because of their mobility impairments and promote their equal participation in society. These results suggest the need for further research on prevailing social attitudes in Nepal toward males with physical disabilities, and the profound impact these factors may have on the lives of these young men. Keywords: Disability, Nepal, mobility impairment, intimate relationship, barriers